Lead Markets in Age-Based Innovations: Demographic Change and Internationally Successful Innovations - Levsen, Nils (Springer, 2015)
Nils Levsen focuses on the international diffusion of product and service innovations for elderly users. In particular, the existence and location of lead markets is being investigated. Lead markets are characterized by their early adoption of innovations and their influence on design choice in a subsequent international diffusion process. Finally, two boundary conditions to the applicability of lead market theory are being identified and described.